QbD-Driven preparation, characterization, and pharmacokinetic investigation of daidzein-l oaded nano-cargos of hydroxyapatite - Namrata Gautam; Debopriya Dutta; Saurabh Mittal; Perwez Alam; Nasr A. Emad; Mohamed H. Al-Sabri; Suraj Pal Verma; Sushama Talegaonkar (Scientific Reports)
Abstract The repercussions of hormone replacement therapy (HRT) and bisphosphonates pose serious clinical challenges and warrant novel therapies for osteoporosis in menopausal women. To confront this issue, the present research aimed to design and fabricate daidzein (DZ); a phytoestrogen-loaded hydroxyapatite nanoparticles to mimic and compensate for synthetic estrogens and biomineralization. Hypothesizing this bimodal approach, hydroxyapatite nanoparticles (HAPNPs) were synthesized using the chemical-precipitation method followed by drug loading (DZHAPNPs) via sorption. The developed nanoparticles were optimized by "Design-Expert" software and underwent comprehensives in-vitro and in-vivo characterizations. The particle sizes of HAPNPs and DZHAPNPs were found to be 118.9 ± 0.15 nm and 129.3 ± 0.65 nm, respectively, consistent with their FESEM and TEM images. A notable entrapment efficiency of 87.23 ± 0.97% and drug release of 91 ± 0.85% from DZHAPNPs was observed over 90 h at pH 7.4. Moreover, the XRD and FTIR results confirmed the amorphization and compatibility of DZHAPNPs. TGA analysis indicated that the thermal stability of blank and drug-loaded nanoparticles was up to 900 °C. In an in vivo pharmacokinetic investigation, three-fold increased bioavailability of DZHAPNPs (AUC0−∞ = 7427.6 µg/mL*h) was obtained in comparison to daidzein solution (AUC0−∞ = 2299.7 µg/mL*h). The comprehensive results of the study indicate that bioceramic nanoparticles are potential carriers for DZ delivery.